Peak age and relative performance progression in international cross-country skiers - Walther, J.; Mulder, R.; Noordhof, D. A.; Haugen, T. A.; Sandbakk, Ø. (International Journal of Sports Physiology and Performance, 2022)
Purpose: To quantify peak age and relative performance progression toward peak age in cross-country skiing according to event type, sex, and athlete performance level.